GAYA BAHASA DALAM ELONG UGI PAMMULANG ELONG (Stylistic Analysis of Elong Ugi Pammulang Elong) - Herianah Herianah (Balai Bahasa Sulawesi Selatan, 2009)
Elong Ugi is a literary work of Buginese which has been famous in the middle of Buginese society since several years ago. Generally, elong Ugi consist of lines called stanza. Line corresponds with the next and forms a unity called stanza. Words used in elong Ugi is figurative language. The way to express feeling and thougt is stylistic. Therefore, this writing discusses about the use of stylistic in elong Ugi Pammulang Elong. Several stylistic of elong found are metaphor, antitesis, hyperbole, metonymy, and repetition.